FOXP2 variation in great ape populations offers insight into the evolution of communication skills. Issue 1 (December 2017) - Staes, Nicky; Sherwood, Chet; Wright, Katharine; Manuel, Marc; Guevara, Elaine; Marques-Bonet, Tomas; Krützen, Michael; Massiah, Michael; Hopkins, William; Ely, John; Bradley, Brenda
Abstract The gene coding for the forkhead box protein P2 (FOXP2 ) is associated with human language disorders. Evolutionary changes in this gene are hypothesized to have contributed to the emergence of speech and language in the human lineage. AlthoughFOXP2 is highly conserved across most mammals, humans differ at two functional amino acid substitutions from chimpanzees, bonobos and gorillas, with an additional fixed substitution found in orangutans. However, FOXP2 has been characterized in only a small number of apes and no publication to date has examined the degree of natural variation in large samples of unrelated great apes. Here, we analyzed the genetic variation in theFOXP2 coding sequence in 63 chimpanzees, 11 bonobos, 48 gorillas, 37 orangutans and 2 gibbons and observed undescribed variation in great apes. We identified two variable polyglutamine microsatellites in chimpanzees and orangutans and found three nonsynonymous single nucleotide polymorphisms, one in chimpanzees, one in gorillas and one in orangutans with derived allele frequencies of 0.01, 0.26 and 0.29, respectively. Structural and functional protein modeling indicate a biochemical effect of the substitution in orangutans, and because of its presence solely in the Sumatran orangutan species, the mutation may be associated with reported population differences in vocalizations.